The Influence of Fintech Adoption and Cashless Payment Behavior on Financial Management Practices in Generation Z - Anggraeni, Sarah; Ganarsih, Inggit (Margin: Jurnal Lentera Managemen Keuangan, 2025)
This study examines the influence of Fintech Adoption and Cashless Payment Behavior on Financial Management Practices in Generation Z, a generation known to be highly adaptive to digital technology. Using a quantitative survey-based approach, this study collected data from respondents aged 21–27 years who represent the profile of Generation Z. The analysis was conducted using the Structural Equation Modeling (SEM) method to identify the relationship between independent and dependent variables. The results of the study indicate that Cashless Payment Behavior has a significant influence on improving financial management, especially through features such as real-time expense tracking and better budget planning. In contrast, Fintech Adoption shows a positive but insignificant relationship to Financial Management Practices, indicating the need for better financial literacy so that financial technology can be utilized optimally. This study emphasizes the importance of developing a digital financial literacy strategy to encourage Generation Z to utilize the potential of financial technology more effectively. In addition, this study opens up opportunities to explore other factors that influence financial management, such as social norms and consumption behavior patterns. These findings provide important contributions for policy makers and financial technology service providers in designing technology-based solutions that are more integrated with the needs of the younger generation in the digital era.